2013
DOI: 10.1254/jphs.13063fp
|View full text |Cite
|
Sign up to set email alerts
|

New Screening System for Selective Blockers of Voltage-Gated K+ Channels Using Recombinant Cell Lines Dying Upon Single Action Potential

Abstract: Abstract. To develop a simple screening system for blockers of voltage-gated Kv1.3 and Kv1.5 channels, new cell lines co-expressing mutated Nav1.5 (IFM/Q3), K ir 2.1 (Kir), and Kv1.3 or Kv1.5 were introduced as IFM/Q3+Kir+Kv1.3 and IFM/Q3+Kir+Kv1.5, respectively. Electrical stimulation (ES) of a cell line, IFM/Q3+Kir, induced prolonged action potentials due to the slow inactivation of IFM/Q3 and subsequent cell death. Additional co-expression of Kv1.3 or Kv1.5 to IFM/Q3+Kir shortened the evoked action potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Recently, several studies suggested the effects of citalopram on ion channels. For example, citalopram inhibited the Kv1.3 and Kv1.5 subtypes in cell lines co-expressing Nav1.5, Kir2.1, Kv1.3, and Kv1.5 [21]. In addition, citalopram inhibited the Nav1.7 and Nav1.8 channels that are expressed in human embryonic kidney (HEK) 293 cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies suggested the effects of citalopram on ion channels. For example, citalopram inhibited the Kv1.3 and Kv1.5 subtypes in cell lines co-expressing Nav1.5, Kir2.1, Kv1.3, and Kv1.5 [21]. In addition, citalopram inhibited the Nav1.7 and Nav1.8 channels that are expressed in human embryonic kidney (HEK) 293 cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…Acacetin has been found to block multiple potassium channels, including cloned Kv1.3 channels expressed in recombinant cell lines [4,5]. The Kv1.3 channel, a member of the Shaker family of potassium channels, is mainly expressed in immune cells such as T cells, macrophages and dendritic cells [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The pipette solution for whole-cell recordings contained (in mM) KCl 140, MgCl 2 4, HEPES 10, Na 2 ATP 2, and EGTA 0.05. The pH of the pipette solution was adjusted to 7.2 with KOH (Fujii et al, 2013). …”
Section: Methodsmentioning
confidence: 99%